2012
DOI: 10.1128/mcb.06547-11
|View full text |Cite
|
Sign up to set email alerts
|

A Balance between Tel1 and Rif2 Activities Regulates Nucleolytic Processing and Elongation at Telomeres

Abstract: Generation of G-strand overhangs at Saccharomyces cerevisiae yeast telomeres depends primarily on the MRX (Mre11-Rad50-Xrs2) complex, which is also necessary to maintain telomere length by recruiting the Tel1 kinase. MRX physically interacts with Rif2, which inhibits both resection and elongation of telomeres. We provide evidence that regulation of telomere processing and elongation relies on a balance between Tel1 and Rif2 activities. Tel1 regulates telomere nucleolytic processing by promoting MRX activity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 52 publications
9
52
0
Order By: Relevance
“…9a). Although we cannot rule out that SAE2 and RIF2 deletions have additive independent effects, this result is in line with the role of Rif2 in regulating the function of MRX/Sae2 in resection 60 . In this case, premature senescence of the rif2D sae2D est2D triple mutant as compared with the sae2D est2D double mutant would suggest that Sae2 is not the only activity inhibited by Rif2.…”
Section: Nature Communications | Doimentioning
confidence: 50%
“…9a). Although we cannot rule out that SAE2 and RIF2 deletions have additive independent effects, this result is in line with the role of Rif2 in regulating the function of MRX/Sae2 in resection 60 . In this case, premature senescence of the rif2D sae2D est2D triple mutant as compared with the sae2D est2D double mutant would suggest that Sae2 is not the only activity inhibited by Rif2.…”
Section: Nature Communications | Doimentioning
confidence: 50%
“…In S. cerevisiae , MRX is known to interact with Rif2, which is recruited to telomeric DNA ends by Rap1 and negatively regulates telomerase action 39404142. Rif2 was recently found to be recruited also to intrachromosomal DSBs in a manner partially dependent on MRX 43.…”
Section: Functional Dynamics Of the Mrx Complexmentioning
confidence: 99%
“…MRX/ MRN is the major responsible for the generation of the G-tail at telomeres, where its activity is stimulated by the PIKK kinase Tel1. 88 Indeed, mrx mutants are defective in G-tail formation in a de novo telomere addition reaction; 89,90 moreover, both mrx mutants and MRN-depleted cells exhibit shorter G-tails. 91,92 Further investigations indicated that MRX and Sae2 act together in the processing the C-strand, even though MRX may give a chromatin remodeler belonging to the Etl1 Snf2 family.…”
Section: Resection In the Telomeric Contextmentioning
confidence: 99%